2003
DOI: 10.1038/sj.bmt.1703810
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic transplantation for multiple myeloma: late relapse may occur as localised lytic lesion/plasmacytoma despite ongoing molecular remission

Abstract: Summary:Allogeneic SCT for myeloma may be curative for young patients, but its role remains controversial because of a reported high TRM in some series. Since 1991, we have performed 25 allografts for myeloma using fully matched sibling donors. Of the 18 evaluable patients, 13 achieved CR at a median time of 2.5 months post-transplant. The five patients who were not in CR when assessed at 3 months received a short course of a-interferon and four subsequently achieved CR with this approach at a median of 82 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…In support of this, Endo et al reported localized relapse of ALL in bone marrow of the extremities (femur and humerus), although relapse from the sternum or iliac bone marrow were also common(18). Bryne et al reported a relapse of multiple myeloma from the humerus where TBI was used as a part of conditioning regimen(19). In addition, little is known about the biology of hematopoiesis in the extremities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this, Endo et al reported localized relapse of ALL in bone marrow of the extremities (femur and humerus), although relapse from the sternum or iliac bone marrow were also common(18). Bryne et al reported a relapse of multiple myeloma from the humerus where TBI was used as a part of conditioning regimen(19). In addition, little is known about the biology of hematopoiesis in the extremities.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well known that relapse of leukemia or multiple myeloma from extremities is rare, several groups reported localized relapse of acute lymphoblastic leukemia (ALL) in bone marrow of extremities(18) or the relapse of multiple myeloma from humerus where TBI was used as a part of conditioning regimen(19). On the other hand, chronic skeletal system complications including avascular bone necrosis and clinically evident osteoporosis have been observed after compensator-based intensity-modulated total body irradiation of 12 Gy(20).…”
Section: Introductionmentioning
confidence: 99%
“…3 Previous reports on the incidence of EM relapse are of MM patients who received an allogeneic MA SCT. Byrne et al 4 published a series of 18 MA-transplanted patients with a follow-up of 5.3 years of whom 7 relapsed. One patient (14%) with a systemic relapse also had an EM localisation (skin).…”
Section: Introductionmentioning
confidence: 99%
“…In this group, we found an overall relapse rate of 55%, which, at the time of analysis was not different between recipients of myeloablative or RIC, perhaps because of the high number of patients treated with CAMPATH in both groups. However, follow‐up is short and it is known that myeloma patients may relapse many years after allogeneic SCT (Byrne et al , 2003).…”
Section: Discussionmentioning
confidence: 99%